Electrochemical decolorization of the reactive orange 16 dye using dimensionally stable Ti/PtOx anode - Mijin Dušan Ž.; Tomić Vuk D.; Grgur Branimir N. (Journal of the Serbian Chemical Society, 2015)
Electrochemical decolorization of the Reactive Orange 16 was studied using dimensionally stable Ti/PtOx anode in the chloride containing solution. Different reaction parameters, agitation speed, applied current, sodium chloride concentration, and dye concentration was varied and optimum electrolysis conditions were suggested. The hypohlorous acid was suggested to be an active species in the electrochemical decolorization. Reaction was also studied using UV-Vis spectrophotometry, high-pressure liquid chromatography (HPLC), and total organic carbon (TOC) and total nitrogen (TN) analyses. [Projekat Ministarstva nauke Republike Srbije, br. ON172013 i br. ON172046]